Association between triglyceride-glucose index and subclinical carotid atherosclerosis in systemic lupus erythematosus: a cohort-based study - Xie, Wenhui; Li, Minjie; Huang, Hong; Fan, Yong; Gao, Dai; Zhang, Jiaying; Zhang, Zhuoli (Frontiers in Immunology, 2025)
ObjectiveTo investigate the association between triglyceride-glucose (TyG) index and carotid atherosclerosis in patients with systemic lupus erythematosus (SLE).MethodsIn this tertiary-center cross-sectional study, 333 consecutive SLE patients undergoing carotid ultrasonography were stratified by TyG index tertiles. The TyG index was calculated as ln[fasting triglycerides (mg/dL) × fasting glucose (mg/dL)/2]. Participants were categorized according to the TyG index tertiles: tertile 1 (<8.25), tertile 2 (8.25–8.69), and tertile 3 (>8.70). Multivariable logistic regression models adjusted for age, sex, body mass index (BMI), comorbidities, low-density lipoprotein cholesterol (LDL-c), statin, and SLE-specific covariates were employed to assess relationships between the TyG index and carotid atherosclerosis/plaque presence.ResultsThe overall rate of carotid atherosclerosis was 10.5% (35/333), with significantly elevated TyG in affected versus unaffected patients (8.77 ± 0.45 vs. 8.45 ± 0.49; p < 0.001). The frequency of carotid atherosclerosis was increased with increases in TyG tertiles (3.6% for tertile 1, 10.0% for tertile 2, and 17.7% for tertile 3; p = 0.003). Each 1-unit TyG increase was associated with a 4.29-fold increased atherosclerosis risk after full adjustment (95% CI 1.47–12.53). Compared to tertile 1, tertile 3 participants exhibited 5.58-fold increased odds of atherosclerosis (95% CI 1.52–20.53; p for trend 0.021). Consistent patterns were observed for carotid plaque outcomes.ConclusionsElevated TyG index independently predicts carotid atherosclerosis risk in SLE populations beyond traditional cardiovascular and lupus-specific confounders. This accessible metabolic biomarker may enhance early atherosclerotic risk stratification in SLE management.